2021
DOI: 10.1016/j.jtbi.2021.110621
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the reproductive number R0 of SARS-CoV-2 in the United States and eight European countries and implications for vaccination

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
83
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 53 publications
15
83
0
2
Order By: Relevance
“…Even so, high seroprevalence levels may reduce the circulation of the virus due to the higher proportion of non-susceptible individuals. Seroprevalence in Spain is far from reaching the herd immunity threshold for COVID-19 (~82.5%), using the mathematical formula 1–1/R0 and assuming an R0 estimate of 5.7 [ 72 , 73 ]. The herd immunity threshold would mean that the incidence of infection will begin to decline once the proportion of individuals with acquired immunity to SARS-CoV-2 in the population exceeds 82.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, high seroprevalence levels may reduce the circulation of the virus due to the higher proportion of non-susceptible individuals. Seroprevalence in Spain is far from reaching the herd immunity threshold for COVID-19 (~82.5%), using the mathematical formula 1–1/R0 and assuming an R0 estimate of 5.7 [ 72 , 73 ]. The herd immunity threshold would mean that the incidence of infection will begin to decline once the proportion of individuals with acquired immunity to SARS-CoV-2 in the population exceeds 82.5%.…”
Section: Discussionmentioning
confidence: 99%
“…6e8 However, the SAR and estimated R 0 were much lower than those of other countries estimated in a previous study (Mean R 0 is 2.5 in Wuhan, China, 5.9 in the United States of America, 3.9 in the United Kingdom, and 4.6 in Italy). 9 This observation suggested that despite the presence of SSEs in Taiwan, the impact of SSEs was mitigated significantly by advanced deployment prevention strategies. Contrariwise, intra-school transmission played an essential role in the explosive community outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…We found 12.8% (95% CI: 11.9 -13.7%) reinfection within one year, and the median reinfection time was 5.1 years (95% CI: 4.7 -5.5 years). It was possible to match the COVID-19 mortality data with the full range of cross-protection strengths between seasonal HCoV and SARS-CoV-2, but the estimated R 0,C19 s were outside of a realistic range for very high values of cross protection, for example, a recent multi-setting study estimating the R 0,C19 to be between 3.6 and 7.3 29 . Cross-protection from seasonal HCoVs to SARS-CoV-2 did not fully explain the apparent reduced susceptibility of children to SARS-CoV-2 observed during the first wave in the UK 17,18,20,21,28 .…”
Section: Discussionmentioning
confidence: 99%